A multi-scale approach for assessing the robustness of cement-based materials from a yield stress perspective. (20th September 2021) - Zuo, Wenqiang; Zhang, Lizhi; Wang, Penggang; Li, Wei; Rong, Hui; She, Wei
Highlights: The robustness of a low-binder content SCC containing different types of powders is studied. A combined yield stress model based on a geometric relation and a first principle model was proposed. The powder packing density and PSD, and the polymer property are the key factors for SCC robustness. Abstract: In practice, the variation of component content can result in unsatisfactory workability in flowable cement-based materials containing multi-components. Hence, the accurate prediction of the rheological property is essential in dealing with such a robustness issue. In the current work, we aim at proposing a generic approach to predict the yield stress of flowable concretes. We first measure the variation of yield stress by tailoring the component content of cement-based materials containing binary blends of powders. The result shows that the yield stress is more sensitive to variations of polymer dosage and water content than variations of powder and aggregate for the given variation range of components. We then combine a geometric relation based on the particle size distribution (PSD) of powders with a recently proposed multi-scale model for the robustness assessment. Our results indicate that by knowing the packing property and size distribution of particles and the chemical property of polymers, the proposed approach can be successfully applied to predict the variation of the yield stress of cement-based materials containing multiple types of powders.